Pengaruh Kepemimpinan Transformasional Terhadap Kepuasan Kerja melalui Budaya Organisasi Pada Lapas Wanita Klas IIA Malang - Eka Sumandary Djaya (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This research purpose is influence of transformational leadership on job satisfaction to corporate culture. the study was conducted at Women’s Prison Class IIA Malang. The subject of this study were 60 employee, using the Partial Least Square (PLS). The result show that transformational leadership on job satisfaction is positive significant, the effect transformational leadership on corporate culture is positive significant, the effect of corporate culture on job satisfaction is positive signicant and the effect corporate culture can mediate transformational leadership on job satisfaction is positive significant.